The possibility of using radiology modalities in the diagnosis of crystalline arthropathy - M. P. Mironov; V. D. Zavadovskaya; M. A. Zorkaltsev; A. P. Kurazhov; S. V. Fomina; O. S. Shulga; T. V. Zhogina; T. B. Perova (Бюллетень сибирской медицины, 2021)
A review of current techniques of instrumental and laboratory diagnosis of crystal arthropathies is presented. Advantages and disadvantages of various methods of diagnostic radiology and diagnostic radiologic criteria employed in primary and differential diagnosis of crystal deposits are discussed in relation to their etiology and clinical peculiarities. It is proven from a wide pool of published studies that the method of ultrasonic diagnosis is the most available one, has no contraindications and demonstrates the best sensitivity and specificity in the diagnosis of crystalline arthropathy.